Challenges and strategies in health workforce management to achieve equitable health care service: A literature review - Donna Ndari Santoso Putri; Nirna Dwi Anggraini; Heri Iswanto (PT WIM Solusi Prima, 2026)
Health is both a basic need and a right of every individual that must be fulfilled to achieve an optimal quality of life. In Indonesia, the availability of healthcare personnel has shown an increase over time, yet it still faces significant challenges regarding equitable distribution. Issues in the distribution of healthcare personnel are inseparable from suboptimal governance aspects. Therefore, this study aims to analyze the challenges and governance strategies for healthcare personnel in supporting equitable health services based on various previous studies. The methods used include a literature review from the Google Scholar, Garuda, and PubMed databases. Based on the findings, it was determined that healthcare workforce governance in Indonesia still faces complex challenges, particularly regarding distribution disparities, shortages of healthcare personnel, and weaknesses in the planning and management of healthcare human resources. Although the number of health workers continues to increase, their distribution remains uneven and is still concentrated in urban areas, leading to disparities in access to health services in remote and underdeveloped regions. It is recommended that the government and stakeholders strengthen health workforce planning based on needs and data, and enhance cross-sectoral coordination in the management of health human resources.